A study on the laser spatter and the oxidation reactions during selective laser melting of 316L stainless steel, Al-Si10-Mg, and Ti-6Al-4V - Simonelli, Marco; Tuck, Christopher; Aboulkhair, Nesma T.; Maskery, Ian; Ashcroft, Ian; Wildman, Ricky D.; Hague, Richard J.M. (Springer, 2015)
The creation of an object by selective laser melting (SLM) occurs by melting contiguous areas of a powder bed according to a corresponding digital model. It is therefore clear that the success of this metal Additive Manufacturing (AM) technology relies on the comprehension of the events that take place during the melting and solidification of the powder bed. This study was designed to understand the generation of the laser spatter that is commonly observed during SLM and the potential effects that the spatter has on the processing of 316L stainless steel, Al-Si10-Mg, and Ti-6Al-4V. With the exception of Ti-6Al-4V, the characterization of the laser spatter revealed the presence of surface oxides enriched in the most volatile alloying elements of the materials. The study will discuss the implication of this finding on the material quality of the built parts.